2004
DOI: 10.1111/j.1442-9993.2004.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of distribution and abundance of chitons of the genus Ischnochiton in intertidal boulder fields

Abstract: Chitons of the genus Ischnochiton are found predominantly on the undersurfaces of boulders, compared with other intertidal or subtidal habitats. They therefore appear to be habitat-specialists at this scale. This, combined with the fact that boulder fields are relatively sparse compared with other intertidal habitats, makes these animals vulnerable to natural and anthropogenic disturbances. In addition, many species of Ischnochiton are relatively rare and appear to have very patchy abundances, making them like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 49 publications
2
35
3
1
Order By: Relevance
“…Similar small-scale patterns of dispersion have also been documented for other taxa living under intertidal and shallow subtidal boulders (see , Chapman 2005. For example, Grayson & Chapman (2004) found that all chitons of the genus Ischnochiton were extremely overdispersed among boulders, such that most of the boulders available were not occupied by chitons, but some boulders had very large abundances of individuals.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Similar small-scale patterns of dispersion have also been documented for other taxa living under intertidal and shallow subtidal boulders (see , Chapman 2005. For example, Grayson & Chapman (2004) found that all chitons of the genus Ischnochiton were extremely overdispersed among boulders, such that most of the boulders available were not occupied by chitons, but some boulders had very large abundances of individuals.…”
Section: Discussionsupporting
confidence: 49%
“…1). The boulder field at Cape Banks is sheltered from direct wave-action except during rough seas and has been described previously by and Grayson & Chapman (2004). The area used in this study was similar to that described in and Grayson & Chapman (2004).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations